The adverse events of haematopoietic stem cell transplantation are associated with gene polymorphism within human leukocyte antigen region - Chen, Ding-Ping (Sci Rep, 2021)
Adverse reactions may still occur in some patients after receiving haematopoietic stem cell transplantation (HSCT), even when choosing a human leukocyte antigen (HLA)-matched donor. The adverse reactions of transplantation include disease relapse, graft-versus-host disease (GVHD), mortality and CMV infection. However, only the relapse was discussed in our previous study. Therefore, in this study, we investigated the correlation between the gene polymorphisms within the HLA region and the adverse reactions of post-HSCT in patients with acute leukaemia (n = 176), where 72 patients were diagnosed with acute lymphocytic leukaemia (ALL) and 104 were acute myeloid leukaemia (AML). The candidate single nucleotide polymorphisms were divided into three models: donor, recipient, and donor-recipient pairs and the data of ALL and AML were analysed individually. Based on the results, we found 16 SNPs associated with the survival rates, the risk of CMV infection, or the grade of GVHD in either donor, recipient, or donor-recipient matching models. In the ALL group, the rs209132 of TRIM27 in the donor group was related to CMV infection (p = 0.021), the rs213210 of RING1 in the recipient group was associated with serious GVHD (p = 0.003), and the rs2227956 of HSPA1L in the recipient group correlated with CMV infection (p = 0.001). In the AML group, the rs3130048 of BAG6 in the donor-recipient pairs group was associated with serious GVHD (p = 0.048). Moreover, these SNPs were further associated with the duration time of survival after transplantation. These results could be applied to select the best donor in HSCT.